Scabies outbreak at the Hospital Víctor Lazarte Echegaray, Trujillo, 2017 - Alfaro Angulo, Marco Antonio (2019)
Objective: To describe the characteristics of a scabies outbreak and assess the effect of the control measures. Materials and methods: A descriptive and prospective epidemiological study was conducted at a reference hospital with220 inpatient beds. Data was collected by visiting the Medicine Service on a daily basis, interviewing the healthcare personnel and examining the medical records. The description of the outbreak includes epidemiological variables such as subject, place and time. Descriptive statistics was used to determine the absolute and relative frequencies, as well as the attack rate. Patients and healthcare personnel were requested to sign an informed consent and received information about the benefits of the research. The intervention consisted of isolation measures and contact transmission-based precautions. The use of non-sterile gloves was emphasized. Results: The outbreak took place between the epidemiological weeks 29 and 37 in the year 2017. The index case was a 93-year-old male patient who had Norwegian scabies and was admitted to the hospital due to Alzheimer’s disease. The scabies occurred in nine female nurses, seven residents, six nurse technicians, one intern y five inpatients. Conclusions: This propagated-source outbreak lasted nine epidemiological weeks; and affected nurses, residents, interns and inpatients. The attack rate was 40 %. The prevention and control measures were isolation of the index case and patients, hand hygiene before and after patient care, use of non-sterile gloves, use of scrubs, use of individual medical supplies for each patient, handling of clothing from scabies-infected patients in sealed bags and using gloves, surface cleaning, withdrawal of scabies-infected health workers from their duties until 24 hours of treatment onset, and epidemiological surveillance. Medical treatment was 5 % permethrin lotion for three days. Use of biosafety standards is recommended for patient care, especially when patients are admitted to the hospital with skin lesions. The implemented measures must be considered to prevent and control this type of outbreak.